Effect of cyclic loading on the microstructure of thin zirconia tapes. Issue 10 (August 2023) - Stastny, Premysl; Chlup, Zdenek; Hlinican, Jan; Kastyl, Jaroslav; Trunec, Martin
Abstract: The effect of cyclic loading on the microstructure and the phase composition of thin zirconia tapes was studied. Zirconium oxide stabilized with 3 mol% of yttrium was used for preparing the tapes by the gel-tape casting method. The static and cyclic strengths of the samples with a thickness of approximately 0.2 mm were tested. The average static strength of 1233 MPa was determined in a three-point bend configuration. The maximal flexural stress during cyclic loading had to be kept below 900 MPa to ensure the failure-free performance of the tapes - (10 7 cycles). No evidence of an excessive transformation of the tetragonal microstructure induced by cyclic loading was found. The transformation toughening mechanism of the tetragonal microstructure was not significantly affected by cyclic loading. Based on the results, thin flexible 3Y-TZP parts possess a low risk of mechanically induced excessive transformational microstructural changes during the service life of the part. Highlights: High-strength flexible 3Y-TZP tapes suitable for manufacturing springs and membranes were used in this cyclic fatigue study. The microstructural investigation found no evidence of the t-m transformation, which could be directly related to the cyclic loading. The tetragonal structure at the tensile surface was stable during cyclic loading without any detectable changes in the phase composition. The microstructural features in the vicinity of the crack were comparable under cyclic and static loading, which implies that the fracture toughening mechanism was not affected by fatigue loading. High-strength flexible ceramic tapes made from 3Y-TZP can be used for the parts undergoing cyclic loading with no dangerous influence of cyclic loading on the transformation toughening effect.